Internal Medicine Clerkship Team-Based Learning Series: Altered Mental Status Module - Steven Bishop; Jeffrey Kushinka; Stephanie Call (Association of American Medical Colleges, 2012)
Abstract This TBL module on Altered Mental Status is one of eight in a series of TBL modules originally designed to complement a clerkship in Internal Medicine for third-year medical students. It focuses on the common causes of altered mental status, strategies for developing the differential diagnosis of the patient with an change in mental status, and the initial evaluation of patients with suspected delirium and dementia. The resource includes the instructor's guide (common to all eight modules), learning objectives specific to the Altered Mental Status module, the iRAT/gRAT (with correct answers bolded and answer explanations), and the group application exercises (again with correct answers bolded and answer explanations). The instructor's guide gives a detailed overview of how to go about implementing the module and where to find more information about TBL if the instructor is using this method for the first time. These modules were originally designed to be utilized in the context of the third-year medical student clerkship in Internal Medicine and are written at that level of complexity. They may be used and would provide an excellent overview of these core topics for learners at any level, however. Additionally, the modules could also be easily adapted for use by Physician Assistant and Nurse Practitioner programs. Each module is designed to take approximately 90 minutes to complete. The modules may be completed in any order by the instructor and do not need to be done sequentially. Each module is an independent topic and does not require knowledge from the other modules in order to be completed by the students. As such, they may be used alone or in any desired combination suitable to the instructor's needs. We have found, however, that utilizing all eight modules over the course of a clerkship period is a comprehensive method of covering the core topic areas and reinforcing knowledge attained by other educational methods during the clerkship (clinical experiences, traditional lecture, independent study, etc.). Prior to each module, the instructor should read the selected portions of Stern et al, 2nd Edition that are also assigned to the students for preparatory work. Additionally, if not familiar with Team-Based Learning, the instructor should read: LK Michaelsen and M Sweet. "The Essential Elements of Team-Based Learning." New Directions for Teaching and Learning, No.116. Winter 2008. Prior to beginning the modules, the students are randomly assigned to equal teams of 5-7 students, as per the recommendations of Team-Based Learning experts. Generally, we have 6 teams of students in our sessions.